Reforming the Apu Trilogy: Reading, Watching, and again Reading Sarbajaya - Hazra, Mousumi (Literary Studies, 2026)
Bibhutibhushan Bandyopadhyay's The Apu Trilogy is one of the canonical references to look back at 1950s rural Bengal, its lives portrayed through the characters fated to tragic destinies and the journey of Apu (the protagonist) through struggles, despair, and misfortune. The novels received worldwide recognition and added several dimensions to it with the cinematic adaptation of Satyajit Ray. The journey from page to screen has been variously experimented with in the hands of Ray. This study aims to reflect on the journey of the trilogy, specifically, the character of Sarbajaya, which is continued in the poem "Me, Sarbajaya" (2021) by Indian poet and translator Zinia Mitra. This paper looks at the transfigurative journey of the character Sarbajaya, who, in the poem, writes a letter to her son Apu, lamenting her last words and her lack of emotional company in her decaying days. "The poem was a direct inspiration of the film, not of the novel," as Mitra has put it. However, apart from an 'unfaithful' adaptation, the poem speaks what is not spoken in the film and the voice that has not been heard yet. I aim to question how poetry, one of the forms of literature, makes the visual character of Sarbajaya 'read' again, with a voice where she speaks of her needs and expectations, and essentially how modernity, which was a thriving zeal for Apu's aspiration, treated Sarbajaya, the Sarbajaya of the poem. In that sense, is it a 'poetic' adaptation, looking back at the source text, therefore, the film, which in turn is adapted from the novel?